2015
DOI: 10.1016/j.diii.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Breast tomosynthesis: Dosimetry and image quality assessment on phantom

Abstract: Doses are significantly greater in 3D than in 2D. With tomosynthesis, out of the three phantoms tested, only phantom BR3D showed a higher rate of visible inserts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Higher absorbed dose values by the breast due to the DBT exam in comparison with the DM exam were reported by the National Health Service Breast Screening Program (NHSBSP) Siemens Mammomat Inspiration digital breast tomosynthesis system (Strudley et al 2015). Doses from DBT higher than from DM can also be seen in other works (Rodríguez-Ruiz et al, 2016;Meyblum et al 2015;Gennaro et al 2018). Baptista et al (2015) also observed that in all 25 projections in the DBT, the organs received higher doses than in DM.…”
Section: Contralateral Breastmentioning
confidence: 76%
“…Higher absorbed dose values by the breast due to the DBT exam in comparison with the DM exam were reported by the National Health Service Breast Screening Program (NHSBSP) Siemens Mammomat Inspiration digital breast tomosynthesis system (Strudley et al 2015). Doses from DBT higher than from DM can also be seen in other works (Rodríguez-Ruiz et al, 2016;Meyblum et al 2015;Gennaro et al 2018). Baptista et al (2015) also observed that in all 25 projections in the DBT, the organs received higher doses than in DM.…”
Section: Contralateral Breastmentioning
confidence: 76%
“…Several parameters influence the MGD of a mammogram. Different MGD are delivered for large CBTs [10,11], for DBT examinations compared to 2D exams, and for MLO (mediolateral-oblique) compared to CC projection. Therefore, the questionnaire specifically requested 20 acquisitions per each 10 mm thickness interval and per projection, for 2D and DBT examinations.…”
Section: Data Collectionmentioning
confidence: 99%
“…Information on the actual breast shape could enhance image processing techniques [1]- [3] and dosimetric estimates [4] in digital mammography (DM) and digital breast tomosynthesis (DBT). For this purpose, we aim to develop an accurate three-dimensional (3D) model of the compressed breast shape for the cranio-caudal (CC) view as well as medio-lateral oblique (MLO) view, obtained during DM and DBT acquisitions.…”
Section: Description Of Purposementioning
confidence: 99%